ENSO‐Driven Variability of Denitrification and Suboxia in the Eastern Tropical Pacific Ocean. Issue 10 (18th October 2017) - Yang, Simon; Gruber, Nicolas; Long, Matthew C.; Vogt, Meike
Abstract : The Eastern Tropical Pacific (ETP) hosts two of the world's three Oxygen Deficient Zones (ODZs), large bodies of suboxic water that are subject to high rates of water column denitrification (WCD). In the mean, these two ODZs are responsible for about 15 to 40% of all fixed N loss in the ocean, but little is known about how this loss varies in time. Here we use a hindcast simulation with the ocean component of the National Center for Atmospheric Research (NCAR) Community Earth System Model over the period 1948 to 2009 to show that the El Niño–Southern Oscillation (ENSO) drives large variations in the rates of WCD in this region. During mature La Niña (El Niño) conditions, peak denitrification rates are up to 70% higher (lower) than the mean rates. This large variability is the result of wind‐driven changes in circulation and isopycnal structure concurrently modifying the thermocline distribution of O2 and organic matter export in such a way that the response of WCD is strongly amplified. During average La Niña (El Niño) conditions, the overall changes in ODZ structure and primarily the shoaling (deepening) of the upper boundary of both ODZs by 40 to 100 m explains 50% of the changes in WCD in the North Pacific and 94% in the South Pacific. Such a large variability of WCD in the ETP has strong implications for the assessments of trends, the balance of the marine N cycle and the emission of the greenhouse gas N2 O. Key Points: ENSO alters water column denitrification in the Eastern Tropical Pacific by up to 70% These changes are driven by variations in oxidant demand and heaving of the oxic‐suboxic boundary The changes in the suboxic zone are primarily caused by wind‐driven variations in tropical circulation